Leaching of bisphenol A from new and old babies' bottles, and new babies' feeding teats - Tan, B.L.L.; Mustafa, A.M. (SAGE Publications, 2003)
Bisphenol A is the monomer used in the manufacture of polycarbonate. Bisphenol A is also known to mimic the female hormone estrogen. In this study, the possibility of the leaching of bisphenol A from polycarbonate babies' bottles and feeding teats was investigated. Bisphenol A was extracted from water samples exposed to the bottles and teats using liquid-liquid extraction. Bisphenol A was analysed by gas chromatograph-mass spectrometer with quadrapole detector in selected ion monitoring mode. Mean leaching of bisphenol A from 100 used babies' bottles when filled with water at 25 degrees C and 80 degrees C were 0.71 +/- 1.65 ng/cm2 (mean +/- standard deviation) and 3.37 +/- 5.68 ng/cm2 respectively. Mean leaching of bisphenol A from 30 new babies' bottles when filled with water at 25 degrees C and 80 degrees C were 0.03 +/- 0.02 ng/cm2 and 0.18 degrees 0.30 ng/cm2 respectively. Bisphenol A was observed to have leached from babies' feeding teats into 37 degrees C water ranged from non-detectable to 22.86 ng/g. The technique employed in this study is fast, reliable and economical.